Evaluation of point‐of‐care International Normalized Ratio in sickle cell disease - Rahman, Syeda (Res Pract Thromb Haemost, 2021)
BACKGROUND: Point‐of‐care (POC) International Normalized Ratio (INR) measurement provides efficient monitoring of warfarin therapy; however, its reliability may be affected in patients with anemia, such as those with sickle cell disease (SCD). OBJECTIVES: To evaluate the correlation of POC‐INR to clinical laboratory INR (CL‐INR) in SCD and use of a correction factor. PATIENT/METHODS: In this retrospective study, the accuracy of POC‐INR compared to CL‐INR was evaluated in a cohort of patients with SCD and in a non‐SCD Black cohort. RESULTS: Despite the difference in anemia, the SCD cohort showed a similar percentage of in‐range POC‐INR values as observed in the non‐SCD cohort (37% vs 42%). The SCD cohort was randomly divided to form discovery and validation cohorts. In the discovery cohort, 86% of POC‐INRs were in range when the POC‐INRs were ˂4.0, but only 24% were in range if POC‐INRs were ≥4.0. A linear regression of CL‐INR versus POC‐INR for POC‐INR values ≥4.0 yielded a coefficient of 0.72 (95% confidence interval, 0.69‐0.75); Multiplying POC‐INR by this correction factor, rounded to 0.7 for ease of use in clinical practice, improved the proportion of in‐range POC‐INR values ≥4.0 from 24% to 100% in the SCD discovery cohort and from 19% to 95% in the SCD validation cohort. Similar findings applied to analyses of the non‐SCD cohort. CONCLUSIONS: POC‐INR and CL‐INR in patients with SCD are similar when POC‐INR is <4.0, and the accuracy of POC‐INR values ≥4.0 can be improved by applying an institution‐specific correction factor.